ASSESSMENT OF HEALTH-RELATED QUALITY OF LIFE AND RISK FACTORS ASSOCIATED WITH PANCREATITIS IN A TERTIARY CARE HOSPITAL - PRASAD TS, DURGA; R, NEHA; R, KALYANI; P, SANDEEP KUMAR; SRI A, JAYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to measure the health-related quality of life (HRQoL) in pancreatitis and to appraise the risk factors associated with the pancreatitis. Methods: A prospective observational study was performed with admitted cases of pancreatitis over 6 month’s period. A total of 150 patients were selected for the study. All data concerning risk factors were recorded and Short-Form-36 (SF-36) questionnaire was applied and quality of life (QOL) was analyzed in all patients with in study group. Results: All domains of (HRQoL) were assessed; it shows highest effect on role limitations due to physical health (36%), role limitations due to emotional problems (29%), role limitations due to physical health, and role limitations due to emotional problems (10%). Finally, our study revealed that there is a profound deterioration in physical components of QOL. The risk factors that majorly influence the QOL in association with disease were found to be alcohol consumption and smoking (70%). Conclusion: Pancreatitis remarkably diminishes the patient’s HRQoL which predominantly shows negative impact on physical health.